Cassette Installation with Active Working Body in the Separating Partition - Nesterenko, Mykola; Nazarenko, Ivan; Molchanov, Petro (International Journal of Engineering and Technology, 2018)
The article explores the vibration form for forming single-type Ferro-concrete products, where the partition walls as an active working body has the opportunity to be involved in resonance oscillations, which allows to reduce the compaction time and reduce the energy costs for manufacturing products. Partitions dynamic characteristics the as well as the effect of the partitions oscillations on the sealing medium are studied mathematically. Â